Strategy Video Games: Some Principles for Teaching - José Miguel Garrido Miranda (Universidad Autónoma de Baja California, 2013)
In order to investigate the reasons that motivate students to play with strategy video games, an analysis of the observed discourse and practices of fifteen Chilean high school students during collective gaming sessions was conducted. By means of an ethno-methodological analysis, we preceded to identify and saturate emerging categories to determine the interests that impel these students to play. The findings, seen from a pedagogical perspective, suggest that the feeling of being part of a scene, solving increasingly complex situations and positively assessing the uncertainty produced by interaction with this type of environment, can become guiding elements for improving the design of teaching situations supported by the use of digital technologies in the classroom.